Transformer Life Prediction Analysis Based on Thermal Aging at PT Ultra Sumatera Dairy Farm - Wageman A. Naiborhu; Haris Gunawan; Zuraidah Tharo (Jurnal Info Sains : Informatika dan Sains, 2026)
A transformer is a vital component in the electrical power distribution system that functions to transfer energy from medium voltage to low voltage. The reliability of a transformer is highly influenced by the thermal condition of its insulation, which determines its service life. This study aims to predict the effective lifespan of a 1250 kVA distribution transformer at PT. Ultra Sumatra Dairy Farm uses the thermal aging method based on the IEEE C57.91-2011 standard. The data used includes nameplate information, daily load profiles, and average ambient temperature. Based on the measurements, the transformer operates at an average load of 422.7 kVA (33.8% of its rated capacity) and an ambient temperature of 23°C. The calculated results show a hottest-spot temperature of 49.55°C with an aging acceleration factor (FAA) of 0.000649. The daily Loss of Life (LOL) value of 0.00000865% indicates that thermal aging occurs very slowly. Based on the Equivalent Aging Factor (FEQA), the theoretical effective lifespan of the transformer reaches approximately 31,660 years. However, in practice, the actual lifespan of the transformer is estimated to range between 25–35 years due to non-thermal factors such as moisture, oil oxidation, and load fluctuations. These results indicate that the thermal condition of the transformer remains very safe and efficient for long-term operation.